Key LogiQL Concepts - Halpin, Terry; Rugaber, Spencer (Taylor & Francis Group, 2015)
LogiQL and its associated execution engine provide you with a powerful way to address your computational needs. Its power arises from its ability to efficiently deal with large amounts of data while avoiding many of the low-level implementation details found in other languages. The language contains a number of intertwined features, and some connections between concepts might not be immediately obvious as you read sequentially through this book. To ease your way, this section provides a brief introduction to the language’s key concepts that you will learn about in subsequent chapters. Each of the mentioned concepts is highlighted in bold and also appears in the Glossary to this book. Be aware that many of these terms have other senses. Further clarification is provided when the concepts are discussed in the chapters.